Analysis of gut microecological characteristics and differences between children with biliary atresia and non-biliary atresia in infantile cholestasis - Liu, Yajun; Zhang, Yuan; Guo, Cheng; Li, Muxia; Wang, Ye; Zhang, Lin (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction:In infants with cholestasis, variations in the enterohepatic circulation of bile acids and the gut microbiota (GM) characteristics differ between those with biliary atresia (BA) and non-BA, prompting a differential analysis of their respective GM profiles. Methods:Using 16S rDNA gene sequencing to analyze the variance in GM composition among three groups: infants with BA (BA group, n=26), non-BA cholestasis (IC group, n=37), and healthy infants (control group, n=50).Additionally, correlation analysis was conducted between GM and liver function-related indicators.Results:Principal component analysis using Bray-Curtis distance measurement revealed a significant distinction between microbial samples in the IC group compared to the two other groups. ICaccumulated co-abundance groups exhibited positive correlations with aspartate aminotransferase, alanine aminotransferase, total bilirubin, direct bilirubin, and total bile acid serum levels. These correlations were notably reinforced upon the exclusion of microbial samples from children with BA.The varying "enterohepatic circulation" status of bile acids in children with BA and non-BA cholestasis contributes to distinct GM structures and functions. This divergence underscores the potential for targeted GM interventions tailored to the specific aetiologies of cholestasis.